Pengaruh Flash Sale Wardah terhadap Impulse Buying Gen Z Pengguna Shopee di Jakarta - Amanda Petra Zefanya; Vita Briliana (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2026)
The rapid expansion of e-commerce in Indonesia is predominantly driven by digitally native Generation Z, who actively engage with platforms such as Shopee. Wardah’s flash-sale strategy—characterized by limited-time offers, substantial discounts, and visually engaging content—effectively stimulates impulse buying; however, the underlying behavioral mechanism remains insufficiently explained. This study investigates the influence of five flash-sale characteristics—information (INF), entertainment (ENT), visuality (VSL), economic benefit (ECB), and price (P)—on attitudes toward flash sales (ATT) and their subsequent effect on impulse buying (IMB) among Gen Z consumers in Jakarta. Employing a quantitative approach with purposive sampling (n = 220), data were analyzed using SmartPLS and SPSS 29. The findings demonstrate that INF, ENT, VSL, and ECB significantly shape ATT, which serves as a key mediating construct driving IMB, while price directly triggers spontaneous purchasing behavior. Theoretically, this study strengthens the Stimulus–Organism–Response framework and the Theory of Planned Behavior by confirming ATT as a central psychological mechanism linking flash-sale stimuli to impulsive responses in Indonesian e-commerce. Managerially, the results emphasize the necessity for Shopee and Wardah to integrate accurate information, interactive entertainment, appealing visuals, clear economic benefits, and strong price and urgency cues to enhance conversions while sustaining Gen Z loyalty over time.